Policy Gaps and Practices on Genetic Diversity, The Heterogenous and Localized Evolutionary Population as well as Native Landraces in Agriculture of Nepal - Joshi, Bal Krishna; Khanal, Subodh; Shrestha, Ram Krishna (Nepal Public Policy Review, 2023)
Formal breeding strategies and processes focus on developing uniform and non-evolutionary populations. However, many farmers continue to cultivate heterogenous cultivars and populations. To understand the recognition of genetic diversity (heterogenous cultivars and populations) in policies and the fields, a literature survey along with field survey, interaction and field action research were carried out in 15 districts of Nepal. Existing policies demand varieties to go through DUS (distinctness, uniformity, stability) testing and be registered in National Seed Board (NSB) for commercial production and sale. This means all native landraces and other broad genetic-based genotypes cannot be marketed without registration. A formal agriculture system accelerates the cultivation of a single genotype in a large area, leading to a lack of pollinators and the loss of many genetic diversities.